Validation of prognostic accuracy of MESH, HKLC, and BCLC classifications in a large German cohort of hepatocellular carcinoma patients. Issue 4 (1st May 2020) - Heinrich, Sophia; Sprinzl, Martin; Schmidtmann, Irene; Heil, Elena; Koch, Sandra; Czauderna, Carolin; Heinrich, Bernd; Philippe P Diggs, Laurence; Wörns, Marcus‐Alexander; Kloeckner, Roman; Galle, Peter R; Marquardt, Jens U; et al.
Abstract : Background and aim: The Barcelona Clinic Liver Cancer (BCLC) staging system is commonly used to classify hepatocellular carcinoma (HCC) patients. However, other staging classification schemes have been proposed. We aimed to compare the prognostic accuracy of the Hong Kong Liver Cancer Staging (HKLC), the Model to Estimate Survival for HCC (MESH), and the BCLC staging systems using a Western cohort of HCC patients. Methods: We retrospectively analyzed 918 patients diagnosed with HCC treated at the University Medical Center of Mainz between 2005 and 2014. We compared the predictive power of survival time of the BCLC, HKLC, and MESH. Predictive ability was tested using the integrated Brier score (IBS) and Harrell's C index. Results: Kaplan–Meier analyses showed significant differences in survival between stages defined by the BCLC, HKLC, and MESH. The HKLC classification demonstrated a more robust classification concordance and lower prediction error compared to the BCLC and MESH. In addition, we found that the BCLC offers superior predictive ability to the MESH in the first four years, whereas the MESH is superior for long‐term predictions. Conclusion: Our analyses confirm the prognostic value of three different HCC scoring systems. When compared, the HKLC provides superior prognostication ability.